Relationship Between Mudskipper (Periophthalmus spp.) Protein Content and Environmental Factors in CMC Tiga Warna Mangrove - Muhammad Fakhrul Rozy; Tyas Nyonita Punjungsari; Didik Wahyudi (Grouper, 2026)
Mudskipper is a brackish water fish with high protein content and potential as an alternative source of protein. One of its natural habitats is the Clungup Mangrove Conservation (CMC) Tiga Warna area. Therefore, this study aimed to analyze the protein content of mudskipper and examine its relationship with environmental factors and sediment organic carbon in the mangrove ecosystem. Samples of mudskipper (Periophthalmus gracilis and Periophthalmus modestus), environmental parameters, and organic carbon were collected using purposive sampling at five stations. Protein content was determined using the Lowry method, while organic carbon was analyzed using the Walkley-Black method. Data were analyzed using ANOVA, and relationships among variables were assessed using Principal Component Analysis (PCA). The results showed that protein content ranged from 11.55% to 18.55%. The highest pH was recorded at station 2 (7.437), temperature at station 1 (30.667°C), dissolved oxygen at station 3 (4.400 mg/L), salinity and total dissolved solids at station 5 (41 ppt; 27,833,333.33 ppm), and organic carbon at station 5 (1.995%). PCA indicated that protein content was positively associated with organic carbon and pH, but not with temperature, salinity, dissolved oxygen, or total dissolved solids. Furthermore, protein content did not significantly differ between species or sampling stations.